Life Expectancy after Bariatric Surgery — the Swedish Obese Subjects Study - Tagliabue, Elena; Ceriani, Valerio; Pontiroli, Antonio E; Gillion, Valentine; Demoulin, Nathalie; Devresse, Arnaud; Carlsson, Lena M.S; Jacobson, Peter; Peltonen, Markku (The New England journal of medicine, 2021)
To the Editor: Carlsson et al. (Oct. 15 issue) 1 provide an update on outcomes from the Swedish Obese Subjects (SOS) study, 2 along with a calculation of life expectancy after bariatric surgery. They report that the effect of bariatric surgery was similar among patients in various age groups. However, the authors do not acknowledge other studies of similar duration. 3 In our meta-analysis involving 607,643 persons, 4 the effect of bariatric surgery appears to be different in various age groups (i.e., greater in persons ≥44 years of age than in those <44 years of age); these results were confirmed in a study involving . . .